PENATALAKSANAAN PEMERIKSAAN CT-SCAN ORBITA MENGGUNAKAN BAHAN KONTRAS DENGAN KLINIS CA SEBASEA - Irma Rahmania (JRI (Jurnal Radiografer Indonesia), 2020)
Background: Orbita CT allows visualization of abnormalities that are not easily seen with konvensional radiography. As a comparison, tomogram are reconstructed by a computer and rotated as anatomical pieces on a monitor. Carcinoma transmits sebaceous is a tumor originating from a malignant sebaceous tumor. This carcinoma usually comes from meibom circles.Research Objectives: To find out the procedure of OrbitaCT-Scan examination using contrast material with clinical Ca Sebaceain Radiology Installation Dr. H. Abdul Moeloek Lampung Province Methods: This study is descriptive qualitative with an observational approach Results: After observation of the obtained results that the examination of CT-Scan Orbita using contrast material is done with special preparations, using pre-contrast and post-contrast axial slice which were then reconstructed into coronal and sagittal slice according to doctor and clinical needs. Conclusions: The results of the picture show suggestive soft tissue tumor maligna in the lateral aspect of the palpebrae sinistra size of 1.9 cm x 3.3 cm x 2.2 cm which appears attached to the lateral aspect of the bulb oculis sinistra.